Enhancing Student’s Collaboration Through A Group Learning in Indonesian Madrasa - Abdul Rohman (FITK UIN Walisongo, 2021)
While madrasa is sometimes regarded as an undeveloped educational institution, it fosters cooperation, a unique quality that may assist students in surviving and succeeding in the twenty-first century. The purpose of this qualitative research is to examine how to improve student collaboration via group learning in madrasa. Documentation, interviews, and observations were used to collect the data. The descriptive-interpretive analysis reveals that madrasa may help students build collaborative attitudes via the use of group learning. Programs implemented as a form of group learning, specifically curriculum design that incorporates the value of collaboration, formation of student research teams, cooperative learning, integration of madrasa-pesantren, habituation, and extra-curricular activities, can improve student’ attitudes toward collaboration.